2020
DOI: 10.1007/s00170-020-04943-5
|View full text |Cite
|
Sign up to set email alerts
|

Rotary compression in tool cavity—a new ductile fracture calibration test

Abstract: Ductile fracture is one of the most common failure modes in hot metal forming. It can be predicted by means of so-called damage functions that describe the relation between stress, deformation and fracture initiation. A practical use of these functions requires the knowledge of the critical damage value of the material that is determined by calibration tests based on compression, tension and torsion. For the prediction to be correct, one must ensure that the modelled and real stresses are in agreement. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…It is also important that the proposed CWR test be compared with previous calibration tests. To this end, one should use the plot made in the η - θ plane ( Figure 18 ) showing the stresses in the CWR test, rotary compression tests [ 17 , 18 ], and classical tests based on tension, compression and torsion [ 57 , 58 ]. The stress in the CWR test was measured with 25 virtual sensors located in the cylindrical section of the specimen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important that the proposed CWR test be compared with previous calibration tests. To this end, one should use the plot made in the η - θ plane ( Figure 18 ) showing the stresses in the CWR test, rotary compression tests [ 17 , 18 ], and classical tests based on tension, compression and torsion [ 57 , 58 ]. The stress in the CWR test was measured with 25 virtual sensors located in the cylindrical section of the specimen.…”
Section: Resultsmentioning
confidence: 99%
“…However, their experiments were limited to the cold forming of steel. Other tests were developed by Pater et al and they were based on the rotary compression of either a disc-shaped specimen in tool cavity [ 17 ] or a cylindrical specimen between two flat plates [ 18 ]. Conducted under hot forming conditions, the tests showed that the critical damage depends greatly on temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the critical damage value rotary compression in a channel 25,26) was performed. During this test the stress state is very similar to the stress state occurring in the process of CR.…”
Section: Determining the Critical Damage Value Of 42crmo4 Grade Steelmentioning
confidence: 99%
“…Before any experimental investigations of cross-wedge rolling were conducted, the process was first simulated, to save resources and time. As mentioned before, finite element analysis (FEA) can accurately depict the CWR process [33,34]. The simulations were calculated within the commercial FEA software Forge NxT 3.0, developed by TRANSVALOR S.A. (CS 40237 Biot, 06904 Sophia Antipolis cedex, France).…”
Section: Cross-wedge Rolling Simulationmentioning
confidence: 99%